Sosialisasi Pemberdayaan Kewirausahaan Berbasis Digital Untuk Meningkatkan Kesejahteraan Ekonomi Masyarakat RW 008, RW 017 dan RW 018 Perumahan Benda Baru, Pamulang – Tangerang Selatan - Erwan Syafri; Rusdi Kurniawan; Haqiqi Lina Layyin; Siti Khoiriah; Anwar Sanusi (Lembaga Pengembangan Kinerja Dosen, 2025)
The Community Service Program titled “Digital-Based Entrepreneurship Empowerment Socialization to Improve the Economic Welfare of the Community in RW 008, RW 017, and RW 018, Benda Baru Housing Complex, Pamulang – South Tangerang” aims to enhance digital literacy and technology-based entrepreneurial skills among local communities, particularly Micro, Small, and Medium Enterprises (MSMEs). This program includes socialization, training, and practical mentoring related to the utilization of social media, e-commerce, Search Engine Optimization (SEO)/Search Engine Marketing (SEM), and digital advertising strategies as tools for business development. The method employed is participatory, actively involving the community in every stage of the program. The results indicate an improvement in community understanding of digital technology and their ability to leverage digital platforms to support their businesses. This program has also successfully created a sustainable digital entrepreneurship ecosystem, which is expected to enhance the economic welfare of the targeted communities. Given its success, this initiative is anticipated to serve as a model for digital-based community empowerment that can be implemented in other regions.